2014
DOI: 10.5657/fas.2014.0067
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition and Stability of Extracted Mackerel Muscle Oil and Oil-Polyethylene Glycol Particles Formed by Gas Saturated Solution Process

Abstract: The oil in mackerel muscle was extracted using an environment friendly solvent, supercritical carbon dioxide (SC-CO 2 ) at a semibatch flow extraction process and an n-hexane. The SC-CO 2 was maintained at a temperature of 45 o C under pressures ranging from 15 to 25 MPa. The flow rate of CO 2 (27 g/min) was constant during the entire 2 h extraction period. The fatty acid composition of the oil was analyzed using gas chromatography (GC). Significant concentrations of eicosapentaenoic acid (EPA) acid and docosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Furthermore, [33] reported that in assessment of oil extracted from marine fishes, polyunsaturated fatty acid was dominated. In the present study, five different polyunsaturated fatty were observed in the fish oil samples by all three extraction methods [34]. Reported higher levels of polyunsaturated fatty acids in Atlantic mackerel.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, [33] reported that in assessment of oil extracted from marine fishes, polyunsaturated fatty acid was dominated. In the present study, five different polyunsaturated fatty were observed in the fish oil samples by all three extraction methods [34]. Reported higher levels of polyunsaturated fatty acids in Atlantic mackerel.…”
Section: Discussionsupporting
confidence: 53%
“…The extractability with SE was 85.6, 83.2 and 87.7% for skins, scales and bones, respectively. This result is a little higher than that of Haque et al (2014), in which they reported extractability as 78.0% for mackerel muscle when they compared HE and SE. The higher extractability might be attributed to optimum conditions used SE and/or nature of sample.…”
Section: Discussionmentioning
confidence: 57%
“…Gas chromatography (GC) analysis was done to determine the fatty acid composition of tuna byproducts oils using the method Haque, Asaduzzaman, and Chun (2014). The analysis was carried out using a 6890 Agilent (Agilent Technologies, Wilmington, NC, USA) gas chromatograph with a fused silica capillary column (100 m length x 0.25 mm internal diameter, 0.2 µm of film) (Supelco, Bellefonte, PA, USA).…”
Section: Fatty Acid Composition Analysismentioning
confidence: 99%
“…Using a gas saturated solution process, employing similar extraction conditions as that of SFE, in mackerel muscle, resulted in a more stable and less oxidized oil. However, the yields were low, obtaining oil concentrations of 4.00 g/20 g of mackerel muscle [83].…”
Section: Application Of Sfe In By-products From Fish Industrymentioning
confidence: 99%